Baseline characteristics of participants in the Kerala Diabetes Prevention Program: a cluster randomized controlled trial of lifestyle intervention in Asian Indians. Issue 5 (15th July 2016) - Sathish, T.; Oldenburg, B.; Tapp, R. J.; Shaw, J. E.; Wolfe, R.; Sajitha, B.; D'Esposito, F.; Absetz, P.; Mathews, E.; Zimmet, P. Z.; Thankappan, K. R.
Abstract: Aims: To describe the baseline characteristics of participants in the Kerala Diabetes Prevention Program. Methods: The Kerala Diabetes Prevention Program is a cluster randomized controlled trial of lifestyle intervention for prevention of Type 2 diabetes mellitus in India. Participants in the study were those aged 30–60 years who had an Indian Diabetes Risk Score ≥ 60 and who were without Type 2 diabetes on oral glucose tolerance test. Data on demographic, lifestyle, clinical and biochemical characteristics were collected using standardized tools. Results: A total of 2586 individuals were screened with the Indian Diabetes Risk Score, of these 1529 people (59.1%) had a score ≥ 60, of whom 1209 (79.1%) underwent an oral glucose tolerance test. A total of 202 individuals (16.7%) had undiagnosed Type 2 diabetes and were excluded, and the remaining 1007 individuals were enrolled in the trial (control arm, n = 507; intervention arm, n = 500). The mean participant age was 46.0 ± 7.5 years, and 47.2% were women. The mean Indian Diabetes Risk Score was 67.1 ± 8.4. More than two‐thirds (69.0%) had prediabetes and 31.0% had normal glucose tolerance. The prevalence of cardiometabolic risk factors was high, including current tobacco use (34.4% in men), current alcohol use (39.3% in men), no leisure time exercise (98.0%), no daily intake of fruit and vegetables (78.7%), family history of diabetes (47.9%), overweight or obesity (68.5%), hypertension (22.3%) and dyslipidemia (85.4%). Conclusions: The Kerala Diabetes Prevention Program recruited participants using a diabetes risk score. A large proportion of the participants had prediabetes and there were high rates of cardiometabolic risk factors. The trial will evaluate the effectiveness of lifestyle intervention in a population selected on the basis of a diabetes risk score. What's new?: Large‐scale use of an oral glucose tolerance test (OGTT) as a prerequisite for entering a diabetes prevention programme is a major financial and practical barrier. The Kerala Diabetes Prevention Program is the first diabetes prevention trial from a low‐ and middle‐income country to use a simple and low‐cost diabetes risk score as a screening tool to identify high‐risk individuals. Of 1209 screen positives, 202 (16.7%) had undiagnosed Type 2 diabetes mellitus on OGTT. The trial will evaluate the effectiveness of lifestyle intervention in a population selected on the basis of a risk score, a large proportion of whom had prediabetes and there were high rates of cardiometabolic risk factors.